2019
DOI: 10.1111/sltb.12589
|View full text |Cite
|
Sign up to set email alerts
|

Caring E‐mails for Military and Veteran Suicide Prevention: A Randomized Controlled Trial

Abstract: Objective The purpose of this multisite study was to conduct a randomized controlled trial of an e‐mail version of the caring letters (CL) suicide prevention intervention to determine whether the intervention is efficacious in preventing suicide behaviors among U.S. service members and veterans. Method Psychiatric inpatients (N = 1,318) were recruited from four military medical centers and two VA hospitals and randomized to receive either 13 caring e‐mails over two years or usual care. Results There were 10 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 35 publications
0
31
0
3
Order By: Relevance
“…In an RCT of CC via text message with service members, Comtois et al (21) found that as an adjunct to outpatient mental health, CC resulted in reduced odds of suicidal ideation and suicide attempt. In an RCT of CC via email with service members and veterans, there were no adverse events and no difference between those who received CC and the control group on death, suicide attempts, or psychiatric readmission (22).…”
Section: Introductionmentioning
confidence: 97%
“…In an RCT of CC via text message with service members, Comtois et al (21) found that as an adjunct to outpatient mental health, CC resulted in reduced odds of suicidal ideation and suicide attempt. In an RCT of CC via email with service members and veterans, there were no adverse events and no difference between those who received CC and the control group on death, suicide attempts, or psychiatric readmission (22).…”
Section: Introductionmentioning
confidence: 97%
“…Intervensi pencegahan bunuh diri pada literature review diberikan dengan durasi yang berbeda-beda. Intervensi pemberian ACT dilakukan selama 7 minggu (Ducasse et al, 2018), intervensi CBT SAFETY dilakukan selama 12 minggu (Asarnow et al, 2015;Asarnow et al, 2017), intervensi DBT dilakukan selama 6 bulan (McCauley et al, 2018), intervensi SOS dilakukan selama 3 bulan (Schilling et al, 2016), intervensi STAT-ED dilakukan selama 2 bulan dan 6 bulan follow up (Grupp-Phelan et al, 2019), intervensi Gratitude diary dilakukan selama 7 hari (Ducasse et al, 2019), intervensi ASSIP dilakukan selama 24 bulan (Michel et al, 2017) dan intervensi caring email (CL) dilakukan selama 2 tahun (Luxton et al, 2020).…”
Section: B Frekuensi Pemberian Intervensiunclassified
“…Intervensi ASSIP diketahui 80% efektif dalam mencegah resiko bunuh diri (Michel et al, 2017). Sedangkan intervensi CL diketahui tidak signifikan dalam pelaporan kejadian bunuh diri dan yang berhubungan dengan resiko bunuh diri (Luxton et al, 2020).…”
Section: Efek Intervensiunclassified
See 2 more Smart Citations